#### Answer

x=7

#### Work Step by Step

Simplifying
-4x + 25 = 6x + -45
Reorder the terms:
25 + -4x = 6x + -45
Reorder the terms:
25 + -4x = -45 + 6x
Solving
25 + -4x = -45 + 6x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-6x' to each side of the equation.
25 + -4x + -6x = -45 + 6x + -6x
Combine like terms: -4x + -6x = -10x
25 + -10x = -45 + 6x + -6x
Combine like terms: 6x + -6x = 0
25 + -10x = -45 + 0
25 + -10x = -45
Add '-25' to each side of the equation.
25 + -25 + -10x = -45 + -25
Combine like terms: 25 + -25 = 0
0 + -10x = -45 + -25
-10x = -45 + -25
Combine like terms: -45 + -25 = -70
-10x = -70
Divide each side by '-10'.
x = 7
Simplifying
x = 7